Genetic Analysis of RAB39B in an Early-Onset Parkinson's Disease Cohort - Gao, Yujing; Wilson, Gabrielle R.; Salce, Nicholas; Romano, Alexandra; Mellick, George D.; Stephenson, Sarah E. M.; Lockhart, Paul J. (Frontiers in Neurology, 2020)
Pathogenic variants in the gene encoding RAB39B resulting in loss of protein function lead to the development of X-linked early-onset parkinsonism. The gene is located within a chromosomal region that is susceptible to genomic rearrangement, and while increased dosage of RAB39B was previously associated with cognitive impairment, the potential role of dosage alterations in Parkinson’s disease (PD) remains to be determined. This study aimed to investigate the contribution of genetic variation in RAB39B to the development of early-onset PD. We performed gene dosage studies and sequence analysis in a cohort of 176 individuals with early-onset PD (age of onset ≤50 years) of unknown genetic aetiology. Assessment of copy number variation over both coding exons and the 3’ untranslated region (UTR) of RAB39B did not identify any alterations in gene dosage. Analysis of the UTRs identified two male individuals carrying single, likely benign, nucleotide variants in the 3’ UTR (chrX:154489749-A-G and chrX:154489197-T-G). Further, one novel variant of uncertain significance was identified in the 5’ UTR, 229 bp upstream of the start codon (chrX:154493802-C-T). In silico analyses predicted that this variant disrupts a highly conserved transcription factor binding site, and could impact RAB39B expression. The results of this study do not support a significant role for genetic variation in RAB39B contributing to early-onset PD, but do highlight that additional molecular studies are required to determine the mechanisms regulating RAB39B expression and their association with disease. Genetic investigations in larger parkinsonism/PD cohorts, and longitudinal studies of individuals with cognitive impairment due to altered dosage of RAB39B, will be required to fully delineate the contribution of RAB39B to parkinsonism.